Dynamics of the seasonal airborne propagation of Staphylococcus aureus in academic dental clinics (Journal of Applied Oral Science, 2022)
Objective: Staphylococcus aureus strains can be disseminated during dental treatments and occasionally lead to the contamination and infection of patients and dentists, which is an important public health problem. The dynamics of the airborne propagation and the genetic diversity of S. aureus isolated in an academic dental clinic environment were investigated using isoenzyme typing. Material and Methods: The isoenzymes of 44 previously reported isolates were obtained from fresh cultures and extracted using glass beads. Nine isoenzymes were investigated using multilocus enzyme electrophoresis (MLEE). The genetic diversity and relationship among the strains (electrophoretic type – ET) were determined using statistics previously described by Nei25 (1972) and the SAHN grouping method (UPGMA algorithm). Results: Clonal pattern analyses indicated a high level of genetic polymorphism occurring among the 33 ETs, which were grouped into five taxa. Each taxon presented one or more clusters that were moderately related and that contained two or more identical/highly related isolates, revealing seasonal airborne propagation in these dental clinic environments. Conclusions: These data suggest the occurrence of active microevolutionary processes in S. aureus as well as the possibility of environmental propagation during a 14-month time span. Such findings are important to show that multiuser academic dental clinics can retain certain strains that are spreadable to different niches.